Serum Malondialdehyde-Modified Low-Density Lipoprotein Level May Be a Biomarker Associated with Aortic Stiffness Among Patients Undergoing Peritoneal Dialysis - Yu-Chi Chang; Chih-Hsien Wang; Chi-Chong Tang; Yu-Li Lin; Yu-Hsien Lai; Chiu-Huang Kuo; Bang-Gee Hsu (Life)
Background: Serum malondialdehyde-oxidized low-density lipoprotein (MDA-oxLDL) is associated with atherosclerosis and increased risk of cardiovascular disease (CVD). Vascular calcification frequently occurs with arterial stiffness in patients on peritoneal dialysis (PD). This cross-sectional study aimed to elucidate the correlation between aortic stiffness and MDA-oxLDL levels in patients on PD. Methods: Overall, 92 patients on PD were included. The carotid–femoral pulse wave velocity (cfPWV) was evaluated using cuff-based volumetric displacement, and blood samples were obtained from all patients. Aortic stiffness was classified based on cfPWV values (>10 m/s indicating aortic stiffness). Serum MDA-ox-LDL levels were quantified using commercial enzyme-linked immunosorbent assay kits. Results: In total, 33 (35.9%) patients were classified into the aortic stiffness group. Factors, including systolic blood pressure (SBP), serum triglyceride levels, C-reactive protein levels, age, weight, body mass index (BMI), waist circumference, MDA-oxLDL levels, and diabetes mellitus (DM) prevalence, were significantly higher in the aortic stiffness group. Multivariable logistic regression analysis revealed significant associations between aortic stiffness and MDA-oxLDL levels, BMI, and SBP. Furthermore, multivariable forward stepwise linear regression analysis revealed serum MDA-oxLDL levels as a significant independent predictor of cfPWV values. Conclusions: Serum MDA-oxLDL levels correlate positively with cfPWV values and may predict aortic stiffness among PD patients, highlighting its potential role in assessing CVD risk in this population.